Tratamientos homeopáticos como alternativa para el control de parásitos Gastrointestinales en bovinos. - Acosta García, Guísela Sofía (2022)
Gastrointestinal parasites (GIP) are one of the most important bovine health problems worldwide, especially subclinical infections, because they cause economic losses by reducing milk and meat production and increase the costs associated with treatment. Most gastrointestinal parasites in cattle are caused by protozoa and worms. Among the protozoa, Eimeria is an enteric coccidioid of the apical complex that causes bovine coccidiosis, an infection clinically characterized by diarrhea, dehydration and death in animals less than one year of age and in immunocompromised animals. The information obtained was carried out through the technique of analysis, synthesis and summary, with the purpose of informing the reader about the use of homeopathic treatments for gastrointestinal parasites in bovines. From the above, it was determined that homeopathy is performed with plant extracts, some pathogens or both, which are used for the control of gastrointestinal parasites in cattle. Homeopathic treatments in gastro intestinal parasites in cattle help us to eliminate these organisms which do not allow our animal to gain body weight. Homeopathic remedies based on plant extracts do not directly try to reduce the parasitic load, but improve the immune response to parasitic infections in cattle. Homeopathic treatments help us to improve the quality and body condition of the animals in our herd and therefore to have better income at the time of selling them. Cina (Artemisia cina) and Neem (Azadirachta indica) are some plants used as homeopathic medicines that have been studied to control gastrointestinal parasites, mainly in cattle. There is a reduction of gastrointestinal parasites (GIP) in calves with the homeopathic treatment of quebracho extract.